Analysis of The Main Character’s Personality Structure in The Short Story Tart di Bulan Hujan by Bakdi Soemanto - Saragih, Rode Arta Yuliani (Lingual Journal of Language and Culture; Vol 17 No 1 (2024): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2024.v17.i01.p07, 2024)
Literary psychology is a type of literary theory that is related to the human psyche. Through literary psychology we can understand the psychology or personality of the characters in a story. This research is aim to analyze the personality structure of the main character, Sum, in the short story Tart di Bulan Hujan by Bakdi Soemanto using Sigmund Freud’s psychoanalytic theory. This research uses qualitative descriptive method and literary psychology approach, Sigmund Freud’s psychoanalysis, to analyze the personality structure of the Id, Ego, and Superego of the main character, Sum, in the short story Tart di Bulan Hujan . The results of this study indicates that the main character, Sum, in her personality shows the three personality structures of Id, Ego, and Superego. Sum’s Id is clearly visible from her strong desire to be able to buy a tart in the rainy month. Then the Ego personality helps the Id to get all its desires in a way that is acceptable in the real world, namely by collecting money by saving and working hard to buy the tart. Meanwhile, Sum’s Superego makes her put aside the Ego and Id. These three-personality structure control the behavior and actions of Sum in making decisions.